Designer artificial membrane binding proteins to direct stem cells to the myocardium. Issue 32 (3rd July 2019) - Xiao, Wenjin; Green, Thomas I. P.; Liang, Xiaowen; Delint, Rosalia Cuahtecontzi; Perry, Guillaume; Roberts, Michael S.; Le Vay, Kristian; Back, Catherine R.; Ascione, Raimomdo; Wang, Haolu; Race, Paul R.; Perriman, Adam W.
Abstract : We present a new cell membrane modification methodology where the inherent heart tissue homing properties of the infectious bacteria Streptococcus gordonii are transferred to human stem cells. Abstract : We present a new cell membrane modification methodology where the inherent heart tissue homing properties of the infectious bacteria Streptococcus gordonii are transferred to human stem cells. This is achieved via the rational design of a chimeric protein–polymer surfactant cell membrane binding construct, comprising the cardiac fibronectin (Fn) binding domain of the bacterial adhesin protein CshA fused to a supercharged protein. Significantly, the protein–polymer surfactant hybrid spontaneously inserts into the plasma membrane of stem cells without cytotoxicity, instilling the cells with a high affinity for immobilized fibronectin. Moreover, we show that this cell membrane reengineering approach significantly improves retention and homing of stem cells delivered either intracardially or intravenously to the myocardium in a mouse model.